2006
DOI: 10.1016/j.msea.2006.06.091
|View full text |Cite
|
Sign up to set email alerts
|

Grain size distribution and heat conductivity of copper processed by equal channel angular pressing

Abstract: ABSTRACT. We report the results of measurements of the grain size distribution function and the thermal conductivity of ultrafine-grained copper produced by equal channel angular pressing (ECAP), with special attention to the evolution of these quantities with the number of pressing cycles. To explain the experimental findings, the equilibrium grain size distribution function (GSDF) evolving during ECAP has been calculated on the basis of a simplified theoretical model. The model involves a single unknown phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
3
17
0
2
Order By: Relevance
“…A log-normal distribution appears to fit the cell size distribution data obtained from TEM analysis pretty well. However, a detailed analysis 6) showed that a different function accounts for the cell size distribution more adequately than a log-normal one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A log-normal distribution appears to fit the cell size distribution data obtained from TEM analysis pretty well. However, a detailed analysis 6) showed that a different function accounts for the cell size distribution more adequately than a log-normal one.…”
Section: Resultsmentioning
confidence: 99%
“…7) can be introduced via the equation As l can be identified with the grain size, and bulk ¼ 400 W/mK and ¼ 39 nm at room temperature 13) are given, the only remaining variable influencing the thermal conductivity is the electron reflectivity. According to, 6) differences in r correspond to differences in the width of grain size distribution functions, as this influences the matching between boundaries of neighboring grains.…”
Section: Effect Of Ecap On Thermal Conductivitymentioning
confidence: 99%
“…Specifically, we observe that the original grain size, (200 to 300) μm, becomes refined to be 600 nm (after 1 pass), 500 nm (after 2 passes), 400 nm (after 4 passes), and 300 nm (after 8 passes). Gendelmana [6] claimed that the small distribution of grain size increases the reflectance of electrons, which eventually decreases the thermal conductivity in ECAP-deformed ultrafine grained coppers. The result of this study with ECAPdeformed ultrafine grained aluminum 1060 agrees with this.…”
Section: Methodsmentioning
confidence: 99%
“…For metal materials, the strength increases with decreasing grain sizes. Use of ECAP has been studied for the grain refinement of metals, including steel, aluminum, and copper [2][3][4][5][6]. In particular, the grain refinement of aluminum alloys below submicron size has been difficult due to the low-temperature recovery with a high stacking fault energy, but ECAP application enables a significant improvement [1].…”
Section: Introductionmentioning
confidence: 99%
“…İnce taneli yapı elde etmek için yapılan çalışmalarda eş kanallı açısal presleme (ECAP) yönteminin kullanımı son on yılda oldukça arttığı görülmektedir. Bakır malzeme için yapılan bir araştırmada plastik deformasyon sırasında malzeme içinde artan dislokasyon yoğunluğu ile malzemenin ısı iletimi ve elektrik iletimi gibi fiziksel özelliklerinin kötüleştiği rapor edilmiştir [12].…”
Section: Tartışma Ve Sonuçunclassified